Nurses' role in the prevention and control of type 2 Diabetes mellitus (Research, Society and Development, 2022)
Introduction: Diabetes Mellitus encompasses a group of metabolic diseases characterized by high blood glucose levels due to defects in insulin secretion and/or action. The nurse role is essential for the maintenance of the individual’s health, from the monitoring of risk factors, control and attention to the complications arising from the disease. Objective: To analyze the scientific evidence about the role of nurses in the prevention and control of type 2 Diabetes Mellitus. Methods: This is a integrative review, carried out from the identification and analysis of data obtained in scientific articles, in which the descriptors “Diabetes Mellitus”, “Nursing Care”, “Disease prevention” were used using the Boolean operator “ and”, selecting studies published in Portuguese, English and Spanish, in the period between 2015 and 2021, in the search platforms Scientific Electronic Library Online (SCIELO), Latin American and Caribbean Literature in Health Sciences (LILACS) via BVS, Us National Library of Medicine National Institutes of Health (Medline-PUBMED), Web of Science, and Nursing Database (BDENF). Results: 2008 articles were found, of which 15 met the inclusion criteria and constituted the sample. The most relevant approaches were to recognize the importance of nursing care in the prevention and control of Diabetes Mellitus, possible strategies and innovative interventions for health promotion. Final considerations: Assistance to patients with Diabetes Mellitus is complex, requires strategies, and the professional nurse integrates the front line for health education, guidelines on treatment and self-care, contributing to minimize risks and complications.